The role of helminth parasites in host invasion: a freshwater fish system - Tierney, Paula Angela (Trinity College Dublin. School of Natural Sciences. Discipline of Zoology, 2021)
With the incidence of species invasions set to increase in the coming decades, it is increasingly important that research on invasive species impacts captures the complexity of natural ecosystems, including the influence of parasites in invasions. Many hypotheses in invasion biology have mixed or no robust empirical support, indicating that these hypotheses may not satisfactorily capture the complex nature of species invasions. Thus, while theoretical and conceptual work are necessary for advancing understanding of parasites in invasions, it is critical that conceptual frameworks are challenged with empirical data to facilitate a truly general and mechanistic understanding of invasion impacts across contexts. This thesis leverages the 100-year range expansion of an invasive freshwater fish as a natural experiment to uncover empirical patterns in helminth parasite communities of invasive and native sympatric hosts, and investigate parasite-mediated impacts of long-established and recently-established invasive host populations. I used a model system of invasive common dace (Leuciscus leuciscus) and native brown trout (Salmo trutta) in Ireland to explore how helminth parasite communities in invasive and native hosts are influenced by host competence (Chapter 2), host colonisation history (Chapter 3), environmental variables and the parasitology of co-occurring hosts (Chapter 4), and host trophic niche (Chapter 5). I also synthesise existing records, and update these with new records of helminth parasites infecting brown trout in Ireland and common dace across its invasive and native ranges.
APPROVED
Keywords: helminths; biological invasion; parasitology; freshwater fish; invasive species; brown trout; leuciscus leuciscus; ecology